TUHAN FAKTA OBJEKTIF: ANALISIS WACANA Al-QUR’AN SURAH Al-FATIHAH AYAT 5 - Hasanuddin Chaer; Abdul Rasyad; Ahmad Sirulhaq (Jurnal Bahasa Lingua Scientia, 2021)
The discourse of this Qur'anic verse invites thought and research of divine psychic that has material space for science. This essay uses the method of approaching social constructionist discourse analysis. This article discusses discourse relating to the divinity and Karl Marx's comments on Religion by title “Religion as the ‘opium of the people’. He said religion is the sigh of the oppressed creature, if people are to know and understand the real world, they must give up superstitious beliefs because they have a narcotic effect on the mind. the first requisite for the happines of the people is the abolition of religion”. The purpose of this article is not to provide evidence of the phenomenon or form of God with material eyes, but to the present relevant contextual discourse about the Al-Qur'an Surah Al-Fatihah verse 5 and a coherent response to Karl Marx's claim to the religion and the divine dimension is forgotten today.